Novel nucleotide triphosphates as potent P2Y2 agonists. - Brookings, D; Davenport, R; Davis, J; Galvin, F; Lloyd, S; Mack, SR; Owens, R; Sabin, V; Wynn, J (2007)
The synthesis and P2Y2 activities of a novel series of nucleoside triphosphates are described. Many of these compounds were potent agonists of the P2Y2 receptor.